Electromyographic study of the trapezius (pars media) and rhomboideus major muscles in movements of the arm (part 1) - DeFreitag, V.; Vitti, M. (My University, 1981)
The participation of the trapezius (pars media) and rhomboideus major muscles in free movements of abduction, adduction, flexion, extension and hyperextension of the arm was studied electromyographically. These muscles were active and synergic in all analysed movements, both acting with intensity that ranged from moderate to very marked.
Keywords: abduction; adduction; arm movement; electromyography; extension; flexion; human cell; muscle; musculoskeletal system; normal human; rhomboideus major muscle; trapezius muscle; Adult; Arm; Electromyography; Human; Male; Movement; Muscle Contraction